Study of writing strategies used by English major students - Syahriani, Syahriani; Madya, Suwarsih (Universitas Pendidikan Ganesha, 2019)
The use of writing strategies has been widely acknowledged to improve students’ writing achievement. Due to lack knowledge of writing strategies, it is important for students to explore their learning strategies in writing. This study is aimed 1) to describe the students’ writing strategies preference; 2) to identify the difference in the writing strategies employed by students in every writing stage. A survey was conducted to one hundred and forty students majoring in English. The participants filled out the Writing Strategies questionnaire. The result indicated that the students’ writing strategies use fell in medium level. Moreover, there is no significant difference on students’ writing strategies used in every writing stage. However, knowing the students preference on writing strategies is beneficial both for students and the teachers.